2012
DOI: 10.1097/igc.0b013e31823b3504
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Frequency of Hydatidiform Mole in Lombardy, Northern Italy, 1996–2008

Abstract: Between 1996 and 2008, the HM incidence in Lombardy showed a slight but significant decrease, mostly owing to the decrease of HM incidence among Asian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…The incidence of hydatidiform mole is varied, ranging from 1.5 to 6 per 1000 pregnancies in North America and Europe; in Italy the estimated frequency of HM over the 1996–2008 time period was 1 case every 935 pregnancies [ 2 , 3 ]. Data for GTN are more limited because the diagnosis is generally made clinically rather than on biopsy material.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of hydatidiform mole is varied, ranging from 1.5 to 6 per 1000 pregnancies in North America and Europe; in Italy the estimated frequency of HM over the 1996–2008 time period was 1 case every 935 pregnancies [ 2 , 3 ]. Data for GTN are more limited because the diagnosis is generally made clinically rather than on biopsy material.…”
Section: Introductionmentioning
confidence: 99%
“…Wide regional variations in the incidence of HM have been reported, ranging from 0.5–1 per 1000 pregnancies in North America, Australia and Europe to 1.5–6 per 1000 pregnancies in South America [ 3 ]. In Italy, the estimated frequency of HM over the 1996–2008 time period was 1 case every 935 pregnancies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 In Italy, the incidence of HM is 1 case in 935 pregnancies. 2 Despite that the majority of molar pregnancies occur in women aged between 20 and 40 years, HM also occurs in older women. Several authors have reported that women older than 40 years are at increased risk of developing a molar pregnancy: at 40 years old, the risk is 1:423 pregnancies, and in women older than 50 years, it becomes 1:8.…”
mentioning
confidence: 99%